Cytotoxic activity of the aqueous extract of Micromeria fruticosa (L.) Druce subsp. serpyllifolia on human U-87 MG cell lines - Koc, Kubra; Ozdemir, Ozlem; Kizilkaya, Omer Faruk; Sengul, Meryem; Turkez, Hasan (Archives of Biological Sciences, 2017)
Micromeria fruticosa (L.) Druce subsp. serpyllifolia, which is widely used in folk medicine as a medicinal herbal tea, is grown in different areas of Turkey and the Mediterranean region. The present study was conducted to evaluate the aqueous extract of Micromeria fruticosa subsp. serpyllifolia for its antioxidant and antiproliferative activity on a human glioblastoma multiforme cell line (U-87 MG), which has not been reported before. Here, the extract was added to cultures at 8 different concentrations (0-200 µg/mL). Cell viability and cell membrane damage was determined using the MTT and LDH assays for 48 h, respectively. To examine the oxidative effects, total antioxidant capacity (TAC) and total oxidant status (TOS) levels were measured. The extract displayed considerable antiproliferative activities at the high concentrations of 175 and 200 µg/mL. Furthermore, the extract caused a signiﬁcant increase in the release of the lactate dehydrogenase (LDH) enzyme in a concentration-dependent manner; 200 µg/mL of extract enhanced the release of LDH. Treatments with extract at higher doses increased TOS levels and decreased TAC levels in human U-87 MG cells. Our study suggests that the aqueous extract of Micromeria fruticosa ssp. serpyllifolia was capable of inducing growth inhibition of cancer cells. These results encourage further research to assess the value of the extract in modern phytotherapy. https://doi.org/10.2298/ABS160504119K Received: May 4, 2016; Revised: May 29, 2016; Accepted: May 30, 2016; Published online: November 4, 2016 How to cite: Koc K, Ozdemir O, Kizilkaya FO, Sengul M, Turkez H. Cytotoxic activity of the aqueous extract of Micromeria fruticosa (L.) Druce subsp. serpyllifolia on human U-87 mg cell lines. Arc Biol Sci. 2017;69(3):449-53.